Contribution of sucrose transporters to phloem unloading within Sorghum bicolor stem internodes. (4th May 2017) - Milne, Ricky J.; Reinders, Anke; Ward, John M.; Offler, Christina E.; Patrick, John W.; Grof, Christopher P.L.
ABSTRACT: Sucrose produced in source leaves is loaded into collection phloem, transported to sinks and unloaded for utilization or storage. In the context of long distance transport, sucrose transporters (SUTs) can function to load sucrose into collection phloem, retrieve leaked sucrose during long distance transport, and load sucrose into sink cells. SUTs have also been proposed to efflux sucrose under conditions of low proton motive force and low extracellular sucrose. The involvement of sucrose transporters in phloem unloading in a representative monocot stem, Sorghum bicolor, was evaluated during different stages of internode development. Transcript levels and functional properties of selected key transporters were measured, with both cellular and subcellular localization determined.